2017
DOI: 10.1161/circep.117.005240
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Idiopathic Left Posterior Fascicular Ventricular Tachycardia

Abstract: The HV interval and 12-lead ECG morphology of LPF-VT may help predict the successful site of origin and prove useful in guiding an effective ablation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Fascicular VT usually presents as an incomplete RBBB morphology with a left-axis configuration and a slightly wider QRSd. 16 For example, for a QRS wave paced at the left posterior fascicle, 17 a small Q wave and tall R wave in leads I and aVL and a small R wave and deep S wave in the inferior leads are often presented. In our study, the paced QRSd was narrow and similar to that of sinus rhythm or mimicked incomplete right bundle branch aberrancy, partially complying with the criteria of VT morphology originating from the left posterior fascicle.…”
Section: Pacing Areamentioning
confidence: 99%
“…Fascicular VT usually presents as an incomplete RBBB morphology with a left-axis configuration and a slightly wider QRSd. 16 For example, for a QRS wave paced at the left posterior fascicle, 17 a small Q wave and tall R wave in leads I and aVL and a small R wave and deep S wave in the inferior leads are often presented. In our study, the paced QRSd was narrow and similar to that of sinus rhythm or mimicked incomplete right bundle branch aberrancy, partially complying with the criteria of VT morphology originating from the left posterior fascicle.…”
Section: Pacing Areamentioning
confidence: 99%
“…In the same context, if the PVC had arisen distal to the LBB, the morphology of the PVC would have caused a wider RBBB pattern and the LBB potential to ventricular interval would have been shorter during the PVC than during the normal QRS complex, because the wavefront propagation would have occurred distal to the LBB and up to the His bundle simultaneously. 2 In our case, the morphology of the PVC exhibited an incomplete RBBB pattern, and compared to the sinus QRS complex, the LBB potential to ventricular interval of the proximal bipolar electrode pair during the PVC decreased from 37 to 32 ms, but on the distal bipolar electrode pair, that interval did not change. According to the formula predicting the earliest presystolic potential of the left fascicular arrhythmia proposed by other investigator, 3 the earliest presystolic potential to ventricular interval during the sinus QRS complex of our case can be predicted as 34.5 ms.…”
Section: A S Ementioning
confidence: 44%
“…The HV interval in LPF-VT may be useful for guiding fascicle mapping base on the electro-anatomical features of the left HPS. 15 In tachycardia, the HV interval is usually described between a positive value and −30 m sec, indicating its origin in the fascicle propagating simultaneously to the His bundle and ventricle. Our study showed the mean HV interval during VT was −12.4 ± 6.9 ms, indicative of Purkinje fiber distribution in the FTs and connection between the fibers in the endocardium and the PMs or adjoining endocardium, contributing to ILVT.…”
Section: Differentiation From Vas Originating From the Pm Myocardiummentioning
confidence: 99%